2010
DOI: 10.5507/euj.2010.008
|View full text |Cite
|
Sign up to set email alerts
|

Physical Disability and Physical Activity: A Review of the Literature on Correlates and Associations

Abstract: The purpose of this article was to examine the literature on correlates and associations of physical activity among adults (age 16-65 years) with physical disabilities. Electronic searches were conducted to identify research articles published from 1980 to 2009. Specific inclusion criteria were identified. The search produced 4,189 articles; however, only 57 met all specified criteria. They represented seven different disability groups, including one cross-over category with two or more disabilities. The Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 64 publications
0
11
0
3
Order By: Relevance
“…Complex barriers challenge efforts to effectively recruit and retain adults with physical disabilities in PA interventions, resulting in small sample sizes (47, 63, 74, 80). Even interventions using convenience samples struggle to reach enrollment targets (15, 33, 90, 100).…”
Section: Pa Promotion Among Individuals With Physical Disabilitiesmentioning
confidence: 99%
“…Complex barriers challenge efforts to effectively recruit and retain adults with physical disabilities in PA interventions, resulting in small sample sizes (47, 63, 74, 80). Even interventions using convenience samples struggle to reach enrollment targets (15, 33, 90, 100).…”
Section: Pa Promotion Among Individuals With Physical Disabilitiesmentioning
confidence: 99%
“…Some authors (Fekete & Rauch, 2012;Mulligan, Hale, Whitehead, & Baxter, 2012;Saebu, 2010) have tried to synthesize this literature within the World Health Organization's (2001) International Classification of Functioning, Disability and Health model (ICF). The ICF is a framework for describing and classifying information on health conditions that takes into account interactions between the condition/disorder/disease, components of functioning (Body Functions and Structures, Activities, and Participation), and contextual factors (Environmental Factors and Personal Factors).…”
Section: Introductionmentioning
confidence: 99%
“…age, selfefficacy, depression and mental health), all of which are significantly correlated with participation in PA in adults with disabilities. 8 Specifically, studies have reported that, in people with disabilities, LTPA was related with life satisfaction, muscle strength, ability to perform everyday activities, and a reduction in secondary conditions. 9e12…”
mentioning
confidence: 99%